2003
DOI: 10.2337/diacare.26.4.1235
|View full text |Cite
|
Sign up to set email alerts
|

Extrapancreatic Autoimmune Manifestations in Type 1 Diabetes Patients and Their First-Degree Relatives

Abstract: OBJECTIVE -To investigate the prevalence of autoimmune diseases in young patients (probands) with type 1 diabetes and their first-degree relatives, and to determine the spectrum of extrapancreatic manifestations in these subjects. RESEARCH DESIGN AND METHODS-The study population included 109 probands age 13 Ϯ 4.9 years and 412 first-degree relatives age 28.7 Ϯ 16.2 years. The prevalence rates of autoimmune thyroiditis and celiac disease were determined in all probands and in 100 of the 412 first-degree relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
1
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 36 publications
8
50
1
9
Order By: Relevance
“…A large body of evidence indicates that inherited genetic factors influence both susceptibility and resistance to the disease. There is significant familial clustering of diabetes mellitus, with an average prevalence risk in siblings of 6% compared to 0.4% in the general population (8,10). In our study population, we detected a family history of DM that is higher than is usually reported.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…A large body of evidence indicates that inherited genetic factors influence both susceptibility and resistance to the disease. There is significant familial clustering of diabetes mellitus, with an average prevalence risk in siblings of 6% compared to 0.4% in the general population (8,10). In our study population, we detected a family history of DM that is higher than is usually reported.…”
Section: Discussioncontrasting
confidence: 43%
“…Its prevalence varies from 8% to 50%, depending on the age, sex and ethnic origin of the subjects. In control populations, antiTPOabs are present in 0-27.0% of patients (8,9,11). It has been reported that follow-up of AIT is important not only for the detection of hypothyroidism, but also for the early diagnosis of papillary carcinoma and thyroid lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As semelhanças no padrão genético de herança e suscetibilidade, além do mecanismo auto-imune compartilhado entre essas endocrinopatias, associadas ao aumento na incidência delas em todo o mundo, têm estimulado pesquisadores a estudar, epidemiologicamente, não só os portadores destas patologias como seus familiares de primeiro grau (4)(5)(6)(7). Estudos mundiais revelam diferentes valores de prevalência de anticorpos antitireoidianos em pacientes com DM1, que variam de 3% a 50% (8).…”
unclassified
“…Twenty five percent of firstdegree relatives of patients with T1DM patients have AIT and up to 6% have CD. 6 These diseases usually occurring together in same individual and having shared genet ic predisposition are associated with organ specific autoantibodies. T1DM is associated with Insulin Auto Antibody (IAA), glutamic acid decarboxylase (GAD) antibody and islet cell antigen [ICA]512 (IA2) antibody; AIT with anti thyroid peroxidase (anti TPO) and anti thyroglobulin (anti TG) antibodies; CD with anti tissue trans glutaminase (anti TTG), endomysial autoantibodies (EMA) and AD with anti 21  hydroxylase auto antibodies.…”
Section: Introductionmentioning
confidence: 99%